2017
DOI: 10.1111/inm.12360
|View full text |Cite
|
Sign up to set email alerts
|

Access to specialist palliative care services by people with severe and persistent mental illness: A retrospective cohort study

Abstract: Compared to the general population, people with pre-existing serious and persistent mental illness (SPMI) have higher rates of physical illness and die at an earlier age, raising questions about their palliative and end-of-life care needs when they are diagnosed with an incurable physical illness. In the present study, we explored access to specialist palliative care services within one New Zealand health district. Routinely-collected, de-identified patient information on a cohort of people diagnosed with SPMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 51 publications
(113 reference statements)
4
84
0
2
Order By: Relevance
“…Health care use in the last year of life (23,24,(33)(34)(35)(36)(25)(26)(27)(28)(29)(30)(31)(32) Hospital (including ICU) (24,(26)(27)(28)(29)(30)(31)(32)35,36) • Rates of hospital admission in the last year of life ranged from 18.7% to 72.6% • Two studies (24,30) reported that people with SMI were more likely to be admitted in the last year of life whilst six studies (27,29,31,32,35,36) reported lower hospital care, although there was great heterogeneity amongst these studies • Mixed evidence was found describing ICU care and other interventions at end of life Emergency department (24,27,28,35) • ED attendance varied according to cause of death and urgency of visit • One study (35) reported more ED attendance in people with SMI and two studies (24,27) reported no difference Palliative care (23,(25)(26)(27)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Health care use in the last year of life (23,24,(33)(34)(35)(36)(25)(26)(27)(28)(29)(30)(31)(32) Hospital (including ICU) (24,(26)(27)(28)(29)(30)(31)(32)35,36) • Rates of hospital admission in the last year of life ranged from 18.7% to 72.6% • Two studies (24,30) reported that people with SMI were more likely to be admitted in the last year of life whilst six studies (27,29,31,32,35,36) reported lower hospital care, although there was great heterogeneity amongst these studies • Mixed evidence was found describing ICU care and other interventions at end of life Emergency department (24,27,28,35) • ED attendance varied according to cause of death and urgency of visit • One study (35) reported more ED attendance in people with SMI and two studies (24,27) reported no difference Palliative care (23,(25)(26)(27)…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported receipt of palliative care (23,(25)(26)(27)29,34), notably four of these were among the most recent studies found in this systematic review of the evidence. Results regarding palliative care were particularly mixed.…”
Section: Palliative Carementioning
confidence: 93%
See 2 more Smart Citations
“…Population-level data from other health systems including Australia and New Zealand support Chochinov's finding that individuals with SMI are 2-4 times less likely than individuals without SMI to access palliative care services in the last months of life. 14,15 Data from studies in Taiwan and France are somewhat more ambiguous: depending on the metrics used and the subgroups studied, palliative care utilization by medically ill patients with SMI could be seen to be either increased or decreased, or both. 16,17 Data from the United States are limited.…”
Section: Current Patterns Of Eol Care For Individuals With Smi: Identmentioning
confidence: 99%